Characterization in aqueous medium of an FMN semiquinone radical stabilized by the enzyme-like microenvironment of a modified polyethyleneimine. Issue 23 (29th May 2020) - Chevalier, Yoan; Lock Toy Ki, Yvette; Herrero, Christian; le Nouën, Didier; Mahy, Jean-Pierre; Goddard, Jean-Philippe; Avenier, Frédéric
Abstract : The elusive flavin semiquinone intermediate found in flavoproteins such as cryptochromes has been obtained in aqueous solution by single electron reduction of the natural FMN cofactor using sodium ascorbate. Abstract : The elusive flavin semiquinone intermediate found in flavoproteins such as cryptochromes has been obtained in aqueous solution by single electron reduction of the natural FMN cofactor using sodium ascorbate. This species was formed in the local hydrophobic microenvironment of a modified polyethyleneimine and characterized by UV-Visible, fluorescence and EPR spectroscopies.